Semisynthesis, Characterization and Evaluation of New Adenosine Derivatives as Antiproliferative Agents - Francisco Valdés Zurita; Nelson Brown Vega; Margarita Gutiérrez Cabrera (Molecules, 2018)
We describe the semisynthesis and biological effects of adenosine derivatives, which were anticipated to function as agonists for the A3 receptor. Molecular docking was used to select candidate compounds. Fifteen nucleoside derivatives were obtained through nucleophilic substitutions of the N6-position of the nucleoside precursor 6-chloropurine riboside by amines of different origin. All compounds were purified by column chromatography and further characterized by spectroscopic and spectrometric techniques, showing moderate yield. These molecules were then evaluated for their antiproliferative activity in human gastric cancer cells expressing the A3 receptor. We found that the compounds obtained have antiproliferative activity and that new structural modifications can enhance their biological activity. The ADME (Absorption, Distribution, Metabolism and Excretion) properties of the most active compounds were also evaluated theoretically.